(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Green Consumerism – a trend topic for present scenario across the globe. It is for the purpose of health consciousness, in efficient habits for health in day today activities, active association of awareness in social media made people to go for green consumerism. Green consumerism is a habit of green food consumption, it should get evolve from the level of education policy. That should include Green Consumerism, habits and its importance.3